GAMBARAN STATUS NUTRISI, POLA KONSUMSI SARAPAN DAN CEMILAN PADA SISWA SEKOLAH DASAR NEGERI 1 GIANYAR - Mirah Sucita Dewi; Luh Seriani (DiscoverSys Inc., 2015)
Breakfast has been known as the most important meal, and it is often missed by children of primary school age and adolescence. Children who eat breakfast regularly have better nutritional profile compared to children who do not eat breakfast. Consumption midmorning snack before lunch is also known in increasing body mass index (BMI).This study is a descriptive cross-sectional approach. Research sample are 5th grade students of SD Negeri 1 Gianyar, located in Puskesmas Gianyar I work area. Total sample was 85 children. Purposive sampling was used as sampling technique by selecting the entire 5th grade students of SD Negeri 1 Gianyar. Data was obtained by questionnaires to the students that were selected as respondents. Data analysis was performed as univariate and bivariate. Study found that almost all (91.80%) samples implemented breakfast behavior, and the rest (8.20%) did not have breakfast. Samples that implemented the behavior of the breakfast, mostly of them had undernutrition status (56.4 %), followed by normal nutritional status (26.9 %) and overnutrition status (16.7%). At samples that eat snacks, most of them had undernutrition status (58.2%), followed by normal nutritional status (26.6 %) and overnutrition status (15.2%).Most of the students of SD Negeri 1 Gianyar had breakfast. Group of students who skipped breakfast and/or skipped snack has higher percentage of normal nutritional status.